Characterization of Campylobacter jejuni proteome profiles in co-incubation scenarios - Dreyer, Annika; Lenz, Christof; Groß, Uwe; Bohne, Wolfgang; Zautner, Andreas Erich (Frontiers in Microbiology, 2023)
In dynamic microbial ecosystems, bacterial communication is a relevant mechanism for interactions between different microbial species. When C. jejuni resides in the intestine of either avian or human hosts, it is exposed to diverse bacteria from the microbiome. This study aimed to reveal the influence of co-incubation with Enterococcus faecalis, Enterococcus faecium, or Staphylococcus aureus on the proteome of C. jejuni 81–176 using data-independent-acquisition mass spectrometry (DIA-MS). We compared the proteome profiles during co-incubation with the proteome profile in response to the bile acid deoxycholate (DCA) and investigated the impact of DCA on proteomic changes during co-incubation, as C. jejuni is exposed to both factors during colonization. We identified 1,375 proteins by DIA-MS, which is notably high, approaching the theoretical maximum of 1,645 proteins. S. aureus had the highest impact on the proteome of C. jejuni with 215 up-regulated and 230 down-regulated proteins. However, these numbers are still markedly lower than the 526 up-regulated and 516 down-regulated proteins during DCA exposure. We identified a subset of 54 significantly differentially expressed proteins that are shared after co-incubation with all three microbial species. These proteins were indicative of a common co-incubation response of C. jejuni. This common proteomic response partly overlapped with the DCA response; however, several proteins were specific to the co-incubation response. In the co-incubation experiment, we identified three membrane-interactive proteins among the top 20 up-regulated proteins. This finding suggests that the presence of other bacteria may contribute to increased adherence, e.g., to other bacteria but eventually also epithelial cells or abiotic surfaces. Furthermore, a conjugative transfer regulon protein was typically up-expressed during co-incubation. Exposure to both, co-incubation and DCA, demonstrated that the two stressors influenced each other, resulting in a unique synergistic proteomic response that differed from the response to each stimulus alone. Data are available via ProteomeXchange with identifier PXD046477.